Formulation Development and Evaluation of Mouth Dissolving Tablet of Aspirin by Using QbD Approach (Dhaka University Journal of Pharmaceutical Sciences, 2021)
In the current investigations, mouth dissolving tablets (MDT) were developed by applying quality by design (QbD) approach. Direct compression method was applied for the preparation of MDT containing aspirin using 32 factorial design with quantity of drug, microcrystalline cellulose (MCC) and crosscarmellose sodium (CCS) as dependant variables. MCC and CCS were used as superdisintegrants. Sodium stearyl fumarate was used as lubricant. Developed MDT were evaluated for characteristics like hardness, friability, disintegration time (DT) and in vitro drug release . Design Expert 11.0 described adequately impact of selected variables (MCC and CCS) at various levels for response under study (DT and friability). The optimized batch showed disintegration time of 15-28 secs, friability within 1% and in vitro drug release of 75-98% after 30 mins, respectively. The present study of experimental design revealed that MCC and CCS are fruitful at low concentration to develop the optimized formulation. As per the results obtained from the experiments, it can be concluded that QbD is an effective and efficient approach for the development of quality into MDT with the application of QTPP, risk assessment and critical quality attributes (CQA).Dhaka Univ. J. Pharm. Sci. 20(1): 19-29, 2021 (June)